Copper‐Catalyzed Enantioselective C1, N‐Dipolar (3+2) Cycloadditions of 2‐Aminoallyl Cations with Indoles. (18th January 2023) - Shen, Lulu; Zheng, Yin; Lin, Zitong; Qin, Tianzhu; Huang, Zhongxing; Zi, Weiwei
Abstract: 2‐Aminoallyl cations are versatile 1, 3‐dipoles that could potentially be used for diverse (3+n) cycloaddition reactions. Despite some preliminary studies, the asymmetric catalytic transformation of these species is still underdeveloped. We herein report a binuclear copper‐catalyzed generation of 2‐aminoallyl cations from ethynyl methylene cyclic carbamates and their enantioselective (3+2) cycloaddition reaction with indoles to construct chiral pyrroloindolines. This transformation features a novel C1, N‐dipolar reactivity for 2‐aminoallyl cations. Abstract : A binuclear copper‐catalyzed (3+2) cycloaddition of 2‐aminoallyl cations with indoles was achieved. This transformation featured a unique C1, N‐dipolar cycloaddition reactivity for 2‐aminoallyl cations. Enantioenriched pyrroloindoline derivatives were prepared by this cycloaddition in high yields with good enantio‐ and diastereoselectivities.